Financial Technology and Inclusion Effects on SME Performance: Moderating Role of Financial Literacy - Prananingrum, Dwi Kartika; Renggaala, Nuniek Yuniarti Ningsih; Rasidun, La Ode; Ridhayantho, Muhamad; Asniar, Nunut (Journal of Business Management and Economic Development, 2026)
This study examines the effects of mobile money, quick response code (QR code), and financial inclusion on the performance of MSMEs in Kendari City, with financial literacy as a moderating variable. Using a quantitative approach with descriptive and explanatory designs, primary data were collected through structured questionnaires distributed to 300 MSME actors selected through purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results show that mobile money, QR code adoption, and financial inclusion have positive and significant effects on MSME performance. In addition, financial literacy amplifies the influence of these variables, indicating that MSME actors with greater financial knowledge are better able to manage transactions, cash flow, and financial decisions effectively. These findings imply that improving MSME performance requires not only broader access to digital financial technology and formal financial services, but also stronger financial literacy among business actors. This study contributes to the literature by confirming the moderating role of financial literacy in the relationship between digital finance, financial inclusion, and MSME performance. However, the study is limited by its cross-sectional design, its restricted scope in Kendari City, and the limited number of variables examined, suggesting that future research should expand the study area, adopt a longitudinal approach, and include additional variables such as innovation, digital capability, and entrepreneurial orientation.